2013
DOI: 10.1016/j.sbspro.2013.06.581
|View full text |Cite
|
Sign up to set email alerts
|

Job Stress Management in Nurses

Abstract: An observational study, including 103 nurses of 2 hospitals in Sanandaj-Iran in 2007, carried out to determine how much nurses coped with their stress and to define the factors affecting stress management. They responded to questionnaires based on Adolescent Coping Orientation for Problem Experiences (A-COPE) with 3-Likert-scale responses. Stress management was positive in 67.9% and negative in 38.8% of nurses. This study showed managing stress depends not only to personality, but also to the work environment.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 10 publications
0
7
0
2
Order By: Relevance
“…In this strategy, stress management aims to decrease physical stress resources in the workplace (17). Laal et al (20) reported that stress management methods had a positive effect on job stress in 67.9% of nurses. Thus, the researchers concluded that job stress-relieving methods were not only related to individuals but also to the job environment.…”
Section: Discussionmentioning
confidence: 99%
“…In this strategy, stress management aims to decrease physical stress resources in the workplace (17). Laal et al (20) reported that stress management methods had a positive effect on job stress in 67.9% of nurses. Thus, the researchers concluded that job stress-relieving methods were not only related to individuals but also to the job environment.…”
Section: Discussionmentioning
confidence: 99%
“…Konuya ilişkin bilimsel yazında, yönetici hemşirelerin iş stres düzeylerini (Göçeri, 2014;Kaneko ve Kakehi 2015;Köse Genç, 2020;Laal, 2013;Miyata ve ark., 2015;Sarıçam, 2012), iş doyumlarını (Acarer ve Beydağ, 2013;Cox, 2019;Özbay, 2007) ve kurumdan ayrılma niyetlerini (Coşkun, 2020;Kantek ve Kartal, 2017) inceleyen birçok çalışma bulunmaktadır. Buna karşın, yönetici hemşirelerin iş stresi düzeylerini, iş doyumu ve kurumdan ayrılma niyetlerinin birlikte incelendiği çalışmaya rastlanmamıştır.…”
Section: Yönetici Hemşirelerin Iş Stresiunclassified
“…Nurses have been shown to work in an environment marked by occupational stressors 2) . Laal 3) examined how nurses cope with daily stress and determined that the percentage of nurses who frequently engaged in positive stress management was low in terms of meeting with friends, listening to music, and playing sports. Also, the study revealed that there were many nurses who frequently opted for negative attempts at stress management in the form of disputing with others, smoking, and overconsuming coffee or alcohol.…”
Section: Introductionmentioning
confidence: 99%